Least-cost solutions to household energy supply decarbonisation in temperate and sub-tropical climates - Vecchi, Andrea; Davis, Dominic; Brear, Michael; Aye, Lu (Journal of cleaner production, 2024)
Decarbonisation of building energy supply is key to achieving current targets of greenhouse gas emission reduction. However, the least-cost, net-zero supply of electrical and thermal loads in residential buildings is affected by building type, local climate and grid emissions intensity and is subject to uncertain future energy prices. This work investigated a typical detached house and an apartment in two climates – temperate and sub-tropical – in Australia. Least-cost optimisation of the technology mixes required to serve building energy loads was undertaken, including a range of appliances powered by electricity, natural gas and hydrogen and the use of distributed energy resourced, notably rooftop solar and residential battery energy storage. Solutions were investigated with increasingly stringent greenhouse gas emission abatement constraints and a range of future prices for electricity and hydrogen, demonstrating: i) progressive electrification is the likely cheapest pathway to net-zero emissions for the two building types studied; ii) should grid decarbonisation lag the abatement constraint applied to the homes, a net-zero dwelling is likely unachievable and the deepest achievable abatement is very expensive; and iii) network-delivered hydrogen may be optimal in a subset of buildings with limited distributed energy resources potential and more peaky heating and hot water demands. In such cases, bio-methane or even synthetic methane may also be preferred. Through significant adoption of distributed energy resources, results suggest an affordable route to deep (i.e. > 50 %) abatement for homeowners that relies less on grid emissions and, beyond the Australian case study, can be extended to a significant proportion of dwellings in other countries. •Least-cost optimisation of energy supply and storage technology mix in dwellings.•Effect of building, climate, energy price, electricity tariff on technology selection.•Usage charge reduces peak by over 2 kWe in fully electrified net-zero dwellings.•H2 or bio-methane sold at up to 70 AUD/GJ can be prospective in a subset of cases.•Rooftop PV and battery cost-effectively reduce emissions by 30–90 % in new builds.